One‐Pot Synthesis of Novel B, N Co–Doped Carbon Materials for High‐Performance Sodium‐Ion Batteries. Issue 21 (4th June 2019) - Hu, Yanping; Shen, Lili; Wei, Xianhua; Long, Zhen; Guo, Xiaoqiang; Qiu, Xiaoqing
Abstract: Boron and nitrogen have been widely utilized as the heteroatoms to prepare boron doped carbon materials for lithium‐ion batteries (LIBs) and supercapacitors since they can act as the electronic acceptor and enhance the electronic conductivity. However, little attention is paid to the coeffect of boron and nitrogen on the performance of carbon materials for sodium‐ion batteries (SIBs). Herein, boron, nitrogen co‐doped carbon materials have been prepared through a facile, environmentally friendly, and cost‐effective one‐pot method, and used as the anode for SIBs. The as‐obtained boron, nitrogen co‐doped carbon materials show a high reversible specific capacity of 329.71 mAh g −1 and a high capacity retention of 91.3% after 100 charge/discharge cycles at a current density of 0.1 A g −1 . The improved electrochemical performance can be ascribed to the enhanced electronic conductivity and double‐layer capacitance behavior by the introduction of boron and nitrogen. The present work demonstrates that boron, nitrogen‐co‐doped carbon is promising anode materials for SIBs, which provides novel insights to the design of carbon anode materials for SIBs. Abstract : Boron, nitrogen‐co‐doped carbon (BNC) is prepared through a facile, environmentally friendly, and cost‐effective one‐pot method, delivering a high reversible specific capacity of 329.71 mAh g −1 after 100 cycles at 0.1 A g −1 with a high capacity retention of 91.3%, which demonstrates that BNC is a promising anode materials for SIBs.